THE IMPORTANCE OF THE MEDITERRANEAN REGION FOR EUROPEAN SECURITY - ARCIPOWSKA Monika (2011)
Security issues in the Mediterranean region are closely related to problems of security and cooperation in Europe. This stems from the fact that the area lies in the vicinity of the European Union so the lack of peace and stability in the region have direct impact on security in Europe. From this perspective, the Mediterranean Basin is a significant challenge for the EU (especially after September 11, 2001). From a geopolitical point of view, it is possible for the EU area to confirm its ability to influence the international arena. Speaking of security in the Mediterranean region in the context of European security, the energy security should also be mentioned. The failure of the Barcelona process showed a lack of effective EU’s partnership strategy for the region. The complexity of the broadly understood security in the Mediterranean region creates a large gap between “abilities and expectations” in the political dialogue. In particular, unsuccessful works towards the adoption of a common Euro-Mediterranean Charter for Peace and Stability prove how difficult is to create an effective political dialogue in the Mediterranean region. To avoid the inefficiency of the Barcelona Process (the lack of symmetry and balance), the EU must draw meaningful conclusions from its mistakes in the past, especially in relation to the future Euro- Mediterranean relations aiming at improvement of the conditions for development. In this context, a new initiative of the Union for the Mediterranean should be considered an opportunity.